Alcoholism as a risk factor for COVID-19: The alcoholic stor - Altable, Marcos; Akram, Muhammad; Iqbal, Mehwish; De la Serna Tuya, Juan Moisés (Ashdin Publishing, 2022)
Alcoholism is a condition associated with psychiatric and psychiatric problems, where the respiratory system is damaged through the mucociliary ladder mechanism and alveolar macrophage dysfunction. In the time COVID-19 has been observed a dramatic increase in alcohol consumption mediated by levels of anxiety and situations of confinement. In this work we analyses the relationship between alcoholism and SARS, especially with SARS-CoV-2, explained by a degradation of the host defenses of the respiratory epithelium by changing the barrier function, the discharge of cytokines and the functions of the cilia. All of them involved in the defense mechanism of the lungs. This leads to a worse prognosis for patients precisely because of alcohol consumption. Based on this approach, alcoholism will exacerbate the consequences of COVID-19.
Keywords: alcohol; COVID-19; cytokine; proinflammatory; SARSCoV-2; storm; Scopus